2017
DOI: 10.1080/00365521.2017.1362466
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and outcomes from Clostridium difficile infection in hospitalized adults with inflammatory bowel disease

Abstract: CDI in IBD patients prolonged hospitalization and increased in-hospital mortality and likelihood of dismissal to a care-facility as compared to IBD patients without CDI. CDI was more common among African-American IBD patients compared to IBD patients of other races.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 43 publications
1
32
0
2
Order By: Relevance
“… 8 A similar study analyzed patients with CDI and IBD using the National Hospital Discharge Survey (NHDS) database from 2005 to 2009. 9 The overall incidence of CDI was 369.8/10,000 IBD hospital admissions, where the incidence in UC admissions was 445.6/10,000 and was significantly higher than Crohn’s disease at 220.3/10,000 admissions ( p < 0.0001).…”
Section: The Burden Of CDI In Ibdmentioning
confidence: 91%
“… 8 A similar study analyzed patients with CDI and IBD using the National Hospital Discharge Survey (NHDS) database from 2005 to 2009. 9 The overall incidence of CDI was 369.8/10,000 IBD hospital admissions, where the incidence in UC admissions was 445.6/10,000 and was significantly higher than Crohn’s disease at 220.3/10,000 admissions ( p < 0.0001).…”
Section: The Burden Of CDI In Ibdmentioning
confidence: 91%
“…Moreover, there is a high prevalence of CDI in asymptomatic patients with IBD . CDI can also influence the disease course of IBD, increase the healthcare costs, and is associated with a worse clinical outcome …”
Section: Introductionmentioning
confidence: 99%
“…Longer the period of hospitalization and higher the severity of the disease, greater was the risk of C. difficile infection among patients in a hospital setting. Moreover, we observed that C. difficile infection in patients with IBD affects the clinical course of IBD and increases the length of hospitalization [ 26 ]. Therefore, it is important in clinical practice to adopt systematized strategies to prevent the vicious cycle of recurrent C. difficile infection superimposed on the disease course in PIBD patients.…”
Section: Discussionmentioning
confidence: 99%